Bisphenol A‐associated alterations in the expression and epigenetic regulation of genes encoding xenobiotic metabolizing enzymes in human fetal liver. (9th November 2013) - Nahar, Muna S.; Kim, Jung H.; Sartor, Maureen A.; Dolinoy, Dana C.; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Alterations in xenobiotic metabolizing enzyme (XME) expression across the life course, along with genetic, nutritional, and environmental regulation, can influence how organisms respond to toxic insults. In this study, we investigated the hypothesis that in utero exposure to the endocrine active compound, bisphenol A (BPA), influences expression and epigenetic regulation of phase I and II XME genes during development. Using healthy 1st to 2nd trimester human fetal liver specimens quantified for internal BPA levels, we examined XME gene expression using PCR Array (n = 8) and RNA‐sequencing (n = 12) platforms. Of the greater than 160 XME genes assayed, 2 phase I and 12 phase II genes exhibited significantly reduced expression with higher BPA levels, including isoforms from the carboxylesterase, catechol O‐methyltransferase, glutathione S‐transferase, sulfotransferase, and UDP‐glucuronosyltransferase families. When the promoters of these candidate genes were evaluated in silico, putative binding sites for the E‐twenty‐six (ETS) and activator protein1 (AP1) related transcription factor families were identified and unique to 97% of all candidate transcripts. Interestingly, many ETS binding sites contain cytosine‐guanine dinucleotides (CpGs) within their consensus sequences. Thus, quantitative analysis of CpG methylation of three candidate genes was conducted across n = 50 samples. Higher BPA levels were associated with increased site‐specific methylation at COMT (P < 0.005) and increased average methylation at SULT2A1 (P < 0.020) promoters. While toxicological studies have traditionally focused on high‐dose effects and hormonal receptor mediated regulation, our findings suggest the importance of low‐dose effects and nonclassical mechanisms of endocrine disruption during development. Environ. Mol. Mutagen. 55:184–195, 2014. © 2013 Wiley Periodicals, Inc.